The Cargill-Type Rearrangement in Natural Product Synthesis - Xun, Wen; Ma, Deyun; Chen, Rimeng; Su, Shaobin; Xu, Bo (Synthesis, 2025)
Natural products are a prolific source of drug leads due to their unique architectures and potent bioactivity. However, their structural complexity often presents formidable challenges for total synthesis. Skeletal editing has recently emerged as a powerful strategy to streamline synthetic routes by selectively reorganizing molecular frameworks. In this context, the Cargill-type rearrangement offers a unique yet underutilized approach to skeletal editing via carbonyl migration. Despite its value, this transformation has not been systematically reviewed. Here, we provide the first focused summary of Cargill-type rearrangements in natural product synthesis, highlighting mechanistic insights and key examples to illustrate their synthetic potential.
Keywords: Cargill-type rearrangement; Skeletal editing; Strain release; Total synthesis; Natural products